Improving Student Learning Outcomes Using the Project-Based Learning (PJBL) Model at SDN 064034 - Br Taringan, Dinda Renita; Saragih, Agung Evansiyus; Hasibuan, Ahmad Laut (PT Inovasi Pratama Internasional, 2025)
This research arises from an awareness of the crucial role education plays in shaping individuals capable of leading better lives and achieving their life goals in alignment with their true purpose. Education is expected to cultivate a generation that excels, can adapt to rapid technological advancements, and enhances learning outcomesparticularly in conceptual understanding, critical thinking, and creativity. The aim of this study is to explore and evaluate the effectiveness of the Project-Based Learning (PjBL) model in improving student learning outcomes at SDN 064034, as a measure of the success of the educational process. However, observations in the field indicate that many students have yet to achieve optimal learning outcomes, largely due to unengaging teaching methods and limited student involvement. As a response, project-based learning is introduced as a strategy to foster active student participation and nurture creativity. Creativity itself is a vital component of both education and modern life, as creative individuals are key to navigating challenges and continuous environmental change.